First successful stabilization of consolidated amorphous calcium phosphate (ACP) by cold sintering: toward highly-resorbable reactive bioceramics. Issue 4 (2nd December 2019) - Luginina, Marina; Orru, Roberto; Cao, Giacomo; Grossin, David; Brouillet, Fabien; Chevallier, Geoffroy; Thouron, Carole; Drouet, Christophe
Abstract : An adequate tuning of amorphous calcium phosphates ionic composition and cold sintering conditions allowed the first successful stabilization of these bioactive compounds. These results show promise for the setup of highly-resorbable bone substitutes. Abstract : In the field of bone regeneration, some clinical conditions require highly-resorbable, reactive bone substitutes to rapidly initiate tissue neo-formation. In this view, Amorphous Calcium Phosphates (ACP) appear as well suited bioceramics taking into account their high metastability. However, the metastability also leads to difficulties of sintering without transformation into crystalline compounds. In this work, various calcium phosphate samples (co)doped with carbonate (CO3 2− ) and magnesium ions were synthesized by the double decomposition method in alkaline media using ammonium and potassium hydroxide solutions. The obtained amorphous powders possess an exceptionally-high carbonate content up to 18.3 wt%. Spark Plasma Sintering (SPS) at very low temperature (150 °C) was then utilized to consolidate initial powders with the view to preserve their amorphous character. The influence of the introduction of different apatite growth inhibitors such as carbonate (CO3 2− ) and magnesium ions was studied. XRD and FTIR analyses revealed that sintered ceramics generally consisted in highly carbonated low-crystallinity apatites, which are expected to have higher solubility than conventional apatite-based systems. However, most interestingly, modulation of the doping conditions allowed us to retain, for the first time, the amorphous character of ACP powders after SPS. Such consolidated ACP compounds may now be considered as a new family of bioceramics with high metastability allowing the fast release of bioactive ions upon resorption.